Challenges of Teachers in Instructional Practices and Job Performance - Edward Jimenez; Raymund Cruz; Sonny N. De Guzman (Asian Journal of Applied Education (AJAE), 2026)
This study aimed to explore the challenges of teachers in instructional practices and their job performance. The results of the study are as follows: there were three (6) major themes identified regarding the challenges encountered by teachers in performing their job-related tasks in schools, (a) recognizing the challenge, (b) experiencing challenges of instructional practice, (c) encountering the most challenging experience, (d) categorizing the nature of instructional practices challenges, (e) mitigation strategies to address challenges, and (f) recognizing the challenges. Based on the findings, it is recommended that teachers may devote more time and give ample assessment recommendations to locate the least learning competencies of the learners, basis for remediation and intervention. Furthermore, their full and strict implementation of the department’s call to concentrate and focus on the pedagogical approaches of teaching specified in the instructional design of curriculum and to continue contextualize the curriculum based on the needs and locality of the learner.